Bibliotherapy Sebagai Upaya Meningkatkan Keterampilan Interpersonal Remaja - Triana Rosalina Noor (Faculty of Ushuluddin and Humanities, 2020)
Literature or books is one of media that used to obtain information, knowledge and self-development. In addition literature also can be used to improve self development, especially teenagers. It becaused some teenagers has not optimize on improving their selves. They still have lack of interpersonal skills that make them difficult to do good adaption in their social environment. Bibliotherapy or or reading therapy is one alternative in dealing with self-development problems. In this way teenagers are expected to develop a more positive sense of themselves, provide insights into a problem, stimulate discussion of problems, provide solutions to problems, communicate new values and attitudes, and discover meaning in life. The choosen process of literature literature based on what problem faced. The goal is the process of reading therapy in order improving teenagers interpersonal skills maximized. In addition, the application of bibliotherapy also consider the interests and learning styles that are owned by teenagers.Bibliotherapy is very effective therapy for improving understanding and adding insight into teenagers according to reading material. Through bibliotherapy, teenagers are expected to find insight over obstacles their selves develompment to improve better interpersonal skills.